A New Method of Solving Diophantine Equation a3 + b3 + c3 = d - Armen A. Avagyan (Изд-во НАН РА)
The article is dedicated to the famous Diophantine equation of the form a3+b3+c3 = d. We solve this problem in some particular cases. Using the package Mathematica 11 we find an e±cient algorithm to solve this problem. This algorithm is simpler and uses a significantly smaller number of operations than the other known algorithms for solving these equations.
Keywords: Mathematics